An introduction to papers from workshops on the evolution of cultural complexity. (October 2020) - Carrignon, Simon; Coto-Sarmiento, María; Bentley, R Alexander; O'Brien, Michael J
Organized as a satellite to the annual Conference on Complex Systems, the Evolution of Cultural Complexity held its inaugural workshop in Tempe, Arizona, in 2015, a second in Cancún, Mexico, in 2017, and a third in Thessaloniki, Greece, in 2018. The goal of those satellite sessions was to bring together a community of researchers from different fields who had interests in the evolution of cultural complexity. This special issue includes three papers that grew out of those workshops and one paper that was solicited. Each brings a unique perspective on myriad issues that surround how and why culture evolves. One issue that is key to understanding the evolution of cultural complexity—and it is addressed in the papers included here—is how humans learn and transmit information and the rate at which it is learned and transmitted.